Improper disposal of solid waste in valley bottom: the case of Mandacaru stream - Polastri, Paula; Orioli, Monigleicia Alcalde; Silveira, Lisyane Wandressa Mazzotti da; Okawa, Cristhiane Michiko Passos; Paredes, Evaristo Atencio; Angelis Neto, Generoso De (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The improper disposal of urban solid waste in valley bottoms contributes to various environmental impacts such as water body and soil contamination, also visual pollution. This work aims to discuss the problem of improper disposal ofurban solid waste in the valley bottoms and describe this waste cleaning process in a stretch of Mandacaru stream, located in Maringá city, PR. The methodology used consisted in visit the study area, identify of improper disposal of waste, classify of waste, and collecting of information from the municipal authorities. The analysis of the results showed the predominance of domestic and non-hazardous wastes disposed inappropriately in two points at Mandacaru stream valley bottom, as well as an amount of 20,65 tons of waste being removed and with final disposal environmentally suitable by the City Government. It can be concluded the need for enforcement of environmental laws associated with the topic, particularly municipal. Still, the implementation of an effective program of environmental education with municipality population, to improve the environmental quality of Mandacaru stream, and the quality of life of the population inhabit the region.